'No freer than the helots': Messenian rebel behaviour in Pausanias' Messeniaka in comparative perspective - Langerwerf, Lydia L.B.M. (2010)
This dissertation explores Pausanias’ depiction of the (mythical) Messenian revolt against the Spartans in book 4 of his Periegesis in comparative perspective with ancient depictions of slave revolts and Flavius Josephus’ Jewish War. I concentrate on how Pausanias portrays Aristomenes and the other rebels, as well as the Messenians in general. Although recently the Messenian Wars have been the subject of scholarly interest from literary critics, historians, and archaeologists, who have fruitfully combined their disciplines in their interpretations of the story, Pausanias’ aims and agenda in his representation of the Messenians have so far been left unexplored. This dissertation therefore asks: What stance did Pausanias take in the contested history of Messenia?